2019
DOI: 10.31026/j.eng.2019.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Water Retention Techniques under Crop’s Root Zone a Tool to Enhance Water Use Efficiency and Economic Water Productivity for Zucchini

Abstract: A new technique in cultivation by installing membrane sheet below the crop’s root zone was helped to save irrigation water in the root zone, less farm losses, increasing the field water use efficiency and water productivity. In this paper, the membrane sheet was installed below the root zone of zucchini during the summer growing season 2017 in open field.  This research was carried out in a private field in Babil governorate at Sadat Al Hindiya Township reached 72 km from Baghdad. Surface trickle irrigation sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The obtained results showed that an increasing value of field water use efficiency in plot T1 was 30.2% comparing with plot T2. Additionally, increasing value in economic water productivity in plot T1 was 36.5% comparing with plot T2 [30].…”
Section: Introductionmentioning
confidence: 87%
“…The obtained results showed that an increasing value of field water use efficiency in plot T1 was 30.2% comparing with plot T2. Additionally, increasing value in economic water productivity in plot T1 was 36.5% comparing with plot T2 [30].…”
Section: Introductionmentioning
confidence: 87%
“…Two plots were used for the comparison plot T1 where the membrane was applied and plot T2 without installing the membrane. The obtained results showed that an increasing value of economic water productivity in plot T1 was 36.5 % higher than in plot T2 [9]. The goal of this paper is to evaluate the effect of applying of the supplementary irrigation on improvement of economic water productivity for winter wheat.…”
Section: Introductionmentioning
confidence: 97%
“…In this research, the WUE and WP for chili peppers inside a greenhouse were computed and compared using 3 methods for chili pepper cultivation: the SWRT technique T1, the organic material T2, and the tillage T3. Hommadi and Almasraf [6] utilized the SWRT membrane sheet to prevent water percolation. This study was located in Sadat Alhindya town in Babylon province, Iraq, using the squash crop, which is cultivated in plots watered via trickle irrigation.…”
Section: Introductionmentioning
confidence: 99%